Trade Liberalization and Growth: New Evidence - Wacziarg, Romain; Horn Welch, Karen (World Bank, 2012)
A new data set of on openness indicators and trade liberalization dates allows the 1995 Sachs and Warner study on the relationship between trade openness and economic growth to be extended to the 1990s. New evidence on the time paths of economic growth, physical capital investment, and openness around episodes of trade policy liberalization is also presented. Analysis based on the new data set suggests that over the 1950–98 period, countries that liberalized their trade regimes experienced average annual growth rates that were about 1.5 percentage points higher than before liberalization. Postliberalization investment rates rose 1.5–2.0 percentage points, confirming past findings that liberalization fosters growth in part through its effect on physical capital accumulation. Liberalization raised the average trade to GDP ratio by roughly 5 percentage points, suggesting that trade policy liberalization did indeed raise the actual level of openness of liberalizers. However, these average effects mask large differences across countries.